Ukraine – Ukrzaliznytsia Modernization Strategy : Policy Note 3 - Selected Cargo Business Issues - World Bank Group (World Bank, Washington, DC, 2019)
The draft law on Railway Transport of Ukraine (the ‘new Railway Law’) is currently awaiting sign-off from other ministries and the approval of the Cabinet of Ministers. The Law, among other aims, is intended to align with commitments contained the EU-Ukraine Association Agreement 2014. The Agreement commits the parties to cooperate and seek to harmonize policy, legislation and regulation across a broad range of areas. In its railway sector, Ukraine undertakes to approximate its legislation to specified EU legislation (the ‘rail acquis’) within stipulated timeframes, generally by 2022. The ‘market opening’ provisions of the new Railway Law will include arrangements allowing properly licensed cargo train operating companies, whether public or private, to provide transport services on Ukraine’s rail network on a fair and equal (competitively neutral) basis. JSC Ukrzaliznytsia has already begun a wide-ranging reform program with its development strategy for 2019-2023 that includes a comprehensive strategy dealing with its vision and values, market analysis, objectives, reorganization into business segments, and actions that are commensurate with best practice observed by the World Bank. The strategy should result in a sustainable and expanding railway to meet the country’s needs. The focus of this policy note is on selected cargo business issues involved in JSC Ukrzaliznytsia (UZ) preparations for competing in the provision of rail cargo transport services.